2005
DOI: 10.1515/hf.2005.100
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships of cadinane-type sesquiterpene derivatives against wood-decay fungi

Abstract: Cadinane-type sesquiterpenes have a wide spectrum of biological activity, but their use as wood preservatives and the structure-activity relationships of their derivatives have not yet been reported. A total of 13 compounds were synthesized from T-cadinol, T-muurolol, and a-cadinol and their chemical structures were confirmed by IR, MS, and 1 H and 13 C NMR. The antifungal properties of 16 compounds against three wood-decay fungi were evaluated in vitro. a-Cadinol showed strong antifungal activity against Lenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…The genera Trametes, Lenzites, and Laetiporus, belong to basidiomycete class, are recognized worldwide as major wood decay fungi (Wu et al, 2005). According to the survey of previous years, tremendous economic and resource losses were caused by fungi and termites in wood biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…The genera Trametes, Lenzites, and Laetiporus, belong to basidiomycete class, are recognized worldwide as major wood decay fungi (Wu et al, 2005). According to the survey of previous years, tremendous economic and resource losses were caused by fungi and termites in wood biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…Also the antifungal activity of cadinene sesquiterpenes against Sclerotium rolfsii ITCC 5313, Rizhoctonia solani ITCC 1742, F. oxysporum ITCC 5365, Macrophomina phaseolina ITCC 5143, has been reported in previous studies (Kundu et al, 2013). In a study conducted by Wu et al (2005), a potential relationship between the chemical structure and the experimentally determined antifungal activity of the cadinenetype sesquiterpene compounds has been demostrated.…”
Section: Tablementioning
confidence: 74%
“…Several studies have demonstrated the properties of sesquiterpenes; their oxygenated forms have a wide spectrum of biological activities, participating as inducers of plant defense mechanisms as well as important antimicrobial properties. This activity has been related with the presence of one or both an unsaturated double bond or oxygen-containing functional group (Kramer and Abraham 2012;Petrelli et al 2016;Wu et al 2005). In plant-microbe associations, sesquiterpenes are crucial for the establishment of the interaction, an example is when Laccaria bicolor interacts with Populus or Arabidopsis plants (Ditengou et al 2015), highlighting the relevance of secondary metabolites in biological interactions.…”
Section: Discussionmentioning
confidence: 99%